Factors associated with alcohol health literacy among patients with diabetes assisted by primary health care - Brito, Ana Monique Gomes; Sousa, Árlen Almeida Duarte de; Vicente, João Victor de Jesus; Alves, Stéfany Allaide Fasolak; Martins, Andréa Maria Eleutério de Barros Lima (ABCS Health Sciences, 2024)
Introduction: The drinking habit is an important factor of metabolic imbalance among people with diabetes. However, individuals with higher levels of health literacy can perform behaviors that create barriers to the emergence of complications of this disease. Checking the health reading related to the drinking habit can be useful to reduce the consequences of diabetes. Objective: To identify the factors associated with health literacy related to the addiction among people with diabetes assisted by primary health care. Methods: Cross-sectional study conducted in health units in the city of Montes Claros, MG, Brazil. Demographic and economic conditions were analyzed, in addition to the levels of health literacy assessed from the instrument Alcohol Health Literacy. Results: The study included 215 people with diabetes with a mean age of 60.73 years, mostly women (63.7%; n=137). Lower levels of alcohol health literacy were present in 31.2% (n=67) of the participants. The following variables were associated with lower levels of health literacy: sex (men, OR 0.46; 95%CI 0.23-0.94; p=0.032), low schooling (early childhood education, OR 7.00; 95%CI 2.55-19.20; p<0.001; illiterate, OR 28.06; 95%CI 4.40-178.83); and spending on diabetes-related drugs (OR 2.27; 95%CI 1.14-4.50; p=0.019). Conclusion: There were better levels of health literacy related to the habit of alcohol use among men, with higher education and who did not have spending on diabetes-related drugs.